Investigation of the Rabotnov-Shesterikov Creep Stability Under General Loading Programs - Trojnacki, A.; Życzkowski, M. (Engineering Transactions, 1976)
The purpose of the present paper is to analyse the critical state of a creeping column, for an arbitrary loading process prescribed either by stresses or by strains. Creep stability in the conditions of pure relaxation is investigated. Some numerical calculations of the critical time for the particular processes are presented. The concept of the boundary process and of the process with safety factors constant in time is introduced. Finally, some remarks concerning the influence of the loading history on the critical time are given.